2007
DOI: 10.1073/pnas.0611693104
|View full text |Cite|
|
Sign up to set email alerts
|

A phase I clinical trial with monoclonal antibody ch806 targeting transitional state and mutant epidermal growth factor receptors

Abstract: An array of cell-surface antigens expressed by human cancers have been identified as targets for antibody-based therapies. The great majority of these antibodies do not have specificity for cancer but recognize antigens expressed on a range of normal cell types (differentiation antigens). Over the past two decades, our group has analyzed thousands of mouse monoclonal antibodies for cancer specificity and identified a battery of antibodies with limited representation on normal human cells. The most tumor-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
136
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(142 citation statements)
references
References 35 publications
(67 reference statements)
6
136
0
Order By: Relevance
“…Thus mAb806 has tumor-specific binding properties and would not be expected to elicit the side effects, including skin rash, observed with other cetuximab-like EGFR targeting (mAbs) associated with targeting of normal tissues. Consistent with these expectations, in a phase I trial, a radiolabeled chimeric version of mAb806 (ch806) demonstrated tumor uptake in multiple tumor types with minimal evidence of normal tissue uptake (11).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Thus mAb806 has tumor-specific binding properties and would not be expected to elicit the side effects, including skin rash, observed with other cetuximab-like EGFR targeting (mAbs) associated with targeting of normal tissues. Consistent with these expectations, in a phase I trial, a radiolabeled chimeric version of mAb806 (ch806) demonstrated tumor uptake in multiple tumor types with minimal evidence of normal tissue uptake (11).…”
Section: Introductionmentioning
confidence: 53%
“…The ability of ABT-806 to cross the BBB and specifically target glioblastoma in patients is supported by the selective imaging of [ 111 In]ABT-806 in a GBM orthotopic mouse model. Phase I clinical observations with both radiolabeled ch806 and ABT-806 also indicate excellent uptake in GBM patients demonstrating that this antibody can effectively cross the BBB or that the BBB is sufficiently comprised in these patients to allow antibody uptake (11,30).…”
Section: Discussionmentioning
confidence: 99%
“…At doses up to 40 mg/m 2 , ch806 was well tolerated; no dose-limiting toxicity was observed and the maximum-tolerated dose was not reached. One case of SD and one progression were registered in the two patients diagnosed with advanced NSCLC [51]. The almost complete absence of EGFRvIII in NSCLC reduces the interest of ch806 in the treatment of NSCLC.…”
Section: Ch806mentioning
confidence: 99%
“…EGFR over-expression and mutation occur in tumor cells but are rare in normal tissues. The results from our completed Phase I clinical trial with a radio-labeled, chimeric version of mAb806 demonstrated that this antibody targets the EGFR on tumors (14). Interestingly, mAb806 also shows synergistic anti-tumor activity in animal models when used in combination with other EGFR therapeutics, including EGFR kinase inhibitors (15) and antibodies to unrelated EGFR epitopes (16).…”
mentioning
confidence: 97%